THE ROUND LIGAMENT IN DEVELOPMENTAL HIP DYSPLASIA: ARE ITS MECHANICAL AND HISTOLOGICAL PROPERTIES PRESERVED? - Zuccon, Alexandre [UNESP]; Pereira, Hamilton Da Rosa [UNESP]; Santos, Sérgio Alexandre Alcântara Dos [UNESP]; Felisbino, Sérgio Luís [UNESP]; Junior, Luís Antônio Justulin [UNESP]; Cataneo, Daniele Cristina [UNESP] (My University, 2022)
Introduction: During open surgical dislocated hip reduction, several anatomical structures, such as the round ligament, are approached. However, there is controversy over both the possibility of preserving the ligament and its functional importance. Materials and Methods: This experimental study used skeletally immature rabbits as a model for congenital hip dislocation. Thirty-six rabbits comprised the sample that was submitted to the round ligament analysis. The sample was stratified for analysis (biomechanics, zymography, histology, and immunohistochemistry). Statistical analysis compared the unstable side to the control side of each rabbit. Results: Biomechanical assays showed that the mean maximal strength of the round ligament on the unstable side was similar to that of the control side (p = 0.594), which was also the case with maximum deformation (p = 0.328). Histologically, there was a statistically significant increase in cellularity on the unstable side (p <0.001). Additionally, there was significantly greater collagen occupancy on the control side (p <0.001). Zymography revealed no significant difference in the amount of active metalloproteinase 2 (MMP-2) (p = 0.068). Conclusions: Although histological analysis found evidence of significant changes in the RL in unstable hips, there were no significant differences in zymography, and no changes were observed in biomechanical tests. Evidence Level V; Experimental study.
O LIGAMENTO REDONDO NA DISPLASIA DO DESENVOLVIMENTO DO QUADRIL: SUAS PROPRIEDADES MECÂNICAS E HISTOLÓGICAS SÃO PRESERVADAS?
Keywords: animal; Coelhos; Collagen; Colágeno; Hip dislocation; Ligamentos redondos; Luxação do quadril; Modelos animais; Models; Rabbits; Round ligaments